CNS Sites Cooperate to Detect Duplicate Subjects with a Clinical Trial Subject Registry. - Shiovitz, Thomas M.; Wilcox, Charles S.; Gevorgyan, Lilit; Shawkat, Adnan (Innovations in Clinical Neuroscience, 2013)
Objective: To report the results of the first 1,132 subjects in a pilot project where local central nervous system trial sites collaborated in the use of a subject database to identify potential duplicate subjects. Method: Central nervous system sites in Los Angeles and Orange County, California, were contacted by the lead author to seek participation in the project. CTSdatabase, a central nervous system-focused trial subject registry, was utilized to track potential subjects at pre-screen. Subjects signed an institutional review board-approved authorization prior to participation, and site staff entered their identifiers by accessing a website. Sites were prompted to communicate with each other or with the database administrator when a match occurred between a newly entered subject and a subject already in the database. Results: Between October 30, 2011, and August 31, 2012, 1,132 subjects were entered at nine central nervous system sites. Subjects continue to be entered, and more sites are anticipated to begin participation by the time of publication. Initially, there were concerns at a few sites over patient acceptance, financial implications, and/or legal and privacy issues, but these were eventually overcome. Patient acceptance was estimated to be above 95 percent. Duplicate Subjects (those that matched several key identifiers with subjects at different sites) made up 7.78 percent of the sample and Certain Duplicates (matching identifiers with a greater than 1 in 10 million likelihood of occurring by chance in the general population) accounted for 3.45 percent of prescreens entered into the database. Many of these certain duplicates were not consented for studies because of the information provided by the registry. Conclusion: The use of a clinical trial subject registry and cooperation between central nervous system trial sites can reduce the number of duplicate and professional subjects entering clinical trials. To be fully effective, a trial subject database could be integrated into protocols across pharmaceutical companies, thereby mandating site participation and increasing the likelihood that duplicate subjects will be removed before they enter (and negatively affect) clinical trials.